2020
DOI: 10.1007/978-3-030-62522-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Bot Log Mining: Using Logs from Robotic Process Automation for Process Mining

Abstract: Robotic Process Automation (RPA) is an emerging technology for automating tasks using bots that can mimic human actions on computer systems. Most existing research focuses on the earlier phases of RPA implementations, e.g. the discovery of tasks that are suitable for automation. To detect exceptions and explore opportunities for bot and process redesign, historical data from RPA-enabled processes in the form of bot logs or process logs can be utilized. However, the isolated use of bot logs or process logs prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In order to see and evaluate the process flow, data must first be extracted from multiple sources, including databases, transaction logs, and other systems, using data mining algorithms. Robotic process automation, or RPA, automates routine, rule-based processes using software robots [22]. RPA may assist firms in locating opportunities for automation and putting automated solutions into place fast and effectively when used in conjunction with process mining.…”
Section: Process Miningmentioning
confidence: 99%
“…In order to see and evaluate the process flow, data must first be extracted from multiple sources, including databases, transaction logs, and other systems, using data mining algorithms. Robotic process automation, or RPA, automates routine, rule-based processes using software robots [22]. RPA may assist firms in locating opportunities for automation and putting automated solutions into place fast and effectively when used in conjunction with process mining.…”
Section: Process Miningmentioning
confidence: 99%
“…The quality and preparation of data for process mining is very time-consuming and, therefore, process mining should provide significant added value and companies should use the insights to take action (De Weerdt and Wynn, 2022;van der Aalst, 2016). Process mining in RPA processes is not very typical at the moment, however, it can be applied to automated processes for RPA (Egger et al, 2020;Průcha, 2021), where duration rates, bottlenecks and deviations can be identified. With advanced methods of process mining such as predictive process monitoring, enhancing the process data with data from other systems, root-cause analysis and online monitoring, it is possible to gain more valuable insights about the behavior of RPA processes including information why an RPA bot fails, whether the bot fails when executing a particular variant and whether RPA bots can keep up with the queue of cases (Burattin, 2022;Di Francescomarino and Ghidini, 2022;Fahland, 2022;Van Houdt and Martin, 2021).…”
Section: Variability and Spc In Process Miningmentioning
confidence: 99%
“…The combined deployment of RPA and process mining could unearth valuable insights into an organization's business processes. On one hand, the data and insights garnered from process mining can be applied across various stages of RPA [22]; on the other, the logs generated can be analyzed using process mining techniques to enhance the understanding of the business processes executed by the RPA bot [23].…”
Section: Literature Reviewmentioning
confidence: 99%